The Development of Copper-Coated Urea for Rice Production - Tai, Kin Leong (2002)

(untitled)
Urea is the main fertilizer used in the rice production in the world. Like other N fertilizers, the efficiency of urea in rice soils generally low due to high losses through volatilization, denitrification and leaching. Slow release fertilizers can be used to minimize loss of N. The rice yields in some area in Malaysia are low due to Cu deficiency. The objective of this study is to develop Cu-coated urea to increase the rice production. In this study, five types of materials consisting chitosan, poly-vinyl chloride (PVC), palm oil sludge (POS), neem oil (NE) and palm stearin (PS) were used as coating materials and Cu carrier. However, due to some technical problems only pos, NE and PS were used in this study. The source of Cu used was copper sulphate. These Cu-coated urea fertilizers were evaluated their effectiveness as Cu carrier and slow-release capabilities in rice soils conditions under laboratory incubation and greenhouse studies using two types of rice soils:- Kangar sries (Typic Endoaquert) and Kundor series (Typic Tropaquept).